Editorial - Wallace, Daniel J. (Current Rheumatology Reviews, 2006)
Scleroderma Associated Inflammatory Arthritis: Common and Painful, but Ignored by Researchers Although the correct term is limited scleroderma, the acronym CREST is still widely used for two reasons. First, CREST is a descriptive and understandable name for five features of scleroderma which are relatively common and frequently concurrent. Secondly, limited scleroderma is associated with pulmonary hypertension and significant nutritional problems which render it hardly “limited”. Whatever the case, while CREST is frequently also associated with inflammatory arthritis, the literature reviewing the nature of this manifestation is scanty. In the report by Restrpo et al., Current Rheumatology Reviews explores this process in CREST in a detail not previously undertaken. First, the widespread association of inflammatory, rheumatoid-like arthritis with CREST is probably greater than appreciated. Secondly, since the process is often erosive and deforming, there is a compelling need to examine this in greater detail. Interestingly, there have been no studies or clinical trials evaluating the best way to manage CREST arthritis. Restropo et al. have performed a service to rheumatology by providing a compelling rationale and précis which clearly demonstrates the need to further elucidate this under investigated process and lure researchers into testing the effectiveness of existing and experimental therapies into managing CREST arthritis.